Effects of the Phytobiotics Ginger Extract (Zingiber Officiale Rosc.) In Drinking Water on KUB Chicken Performance - Ningsih, Niati; Syaikhullah, Gayuh; Adhyatma, M.; Rofiqi, Zainur; Al Huzaini, Mohammad Fadil (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The present study was to evaluate the effects of phytobiotics ginger (Zingiber officinale Rosc.) in drinking water on productive traits Kampung Unggul Balitbangtan (KUB) chickens.  A total number of one hundred KUB chicks were randomly divided into four treatments with five replicates, each replicate contained five chickens. KUB chickens have received a basal diet supplemented with or without experimental treatments. Five experimental treatments were: control diet (T0), drinking water with 0.5% red ginger extract (T1), 1.0 % red ginger extract (T2), and 1.5 % red ginger extract (T3).  The experimental treatments were controlled without red ginger extract (T0), drinking water with 0.5%  ginger extract (T1), 1.0 % ginger extract (T2), and 1.5 % ginger extract (T3). The basal diet was yellow corn, BR2 poultry concentrate produced by PT Wonokoyo, rice brand, and vitamin premix, which contains 17.07% CP, 3097.79 kcal/kg ME, 0.81% Ca, and 0.56% Pav.  Variables evaluated were productive traits of KUB chicken. Data were statistically analyzed using ANOVA in a completely randomized design. The conclusion of this research was phytobiotic ginger extract in the drinking water did not significantly affect the performance productivity of KUB chicken.